Development of Natural Science Learning Designs to Improve The Character of Pancasila Students in Critical and Creative Reasoning Aspects - Rinnanik; Rachmawati Novaria; Agus Mukholid; Aditia Fradito (Postgraduate, University of Mataram, 2023)
The application of values in learning activities is an effort to strengthen student character. This effort is in line with the Ministry of Education and Culture's commitment to realizing Pancasila Students. Pancasila students are the embodiment of Indonesian students who have good character with competencies that can compete globally and reflect the noble values of Pancasila in every behavior. The results of a preliminary study on science learning activities at Arafah Elementary School show the low level of Pancasila student character in the critical and creative reasoning aspects of students. There is a need for alternative learning designs that are able to accommodate the character of Pancasila students in the aspects of students' critical and creative reasoning skills. This research is development research using the Learning Development Cycle (LDC) model. Model cycle This research includes the scope, creation, user experience, meta stages evaluation, and evaluation. This research aims to describe the development product in the form of a science learning design in improving the character of Pancasila students in the aspects of critical and creative reasoning. The product description is reviewed based on the data obtained, namely the results of product validation provided by experts with valid criteria if it reaches the valid-very valid category, data on effectiveness results is reviewed from the achievement of critical and creative reasoning indicators through pretest and posttest with effective criteria if it reaches the medium- high, and practicality is reviewed based on the observer's assessment of implementation with practical criteria if it reaches the practical-very practical category.